Comparative Study of Personality Traits & Values of the Students at Senior Secondary Level: Exploring the Impact of Education on Personality Development (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Personality refers to "that which permits aprediction of what a person will do in a given situation. The goal ofpsychological research in personality is to establish laws about, what differencewill do in all kinds of social and general environmental situations.Personality is concerned with all the behaviour of the individual both over andunder the skin. As the human civilization developed with the long passage oftime, human starts to collect the knowledge, to transmit the accumulatedknowledge to its younger generation and to enhance the present knowledge offield. This process is related keenly to the development of human race.Gradually man’s society starts to establish various agencies and organisationsfor the all-round training of the younger generation. This process is callededucation which means the all-round development of the personality. Thiseducation process aims at the complete development of the personality. It tendsto develop the child physically, mentally, socially, morally, spiritually,intellectually and preparing individual a responsible member of his society. Toaccomplish these objectives society has established various educationalagencies, and organization.